2017
DOI: 10.1007/s10689-017-9985-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and clinical interpretation of BRCA1/BRCA2 variants in families from Murcia (south-eastern Spain) with hereditary breast and ovarian cancer: clinical–pathological features in BRCA carriers and non-carriers

Abstract: This is the first study performed in Murcia (south-eastern Spain) in which 592 families with hereditary breast and ovarian cancer were identified thanks to Genetic Counselling Units from this area over 6 years. Diagnostic performance was 18.1% and 194 different genetic variants were obtained. Variants with uncertain significance accounted for only 5.6% of the total number of reports, so our population has been well characterised. In BRCA1 gene, two novel variants were found (c.1859delT and c.3205C > T) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…Mutations in BRCA1 and BRCA2 genes were identified in 16% of families (26% of individuals) included in the high-risk HBOC sample. This rate is comparable with other studies [14, 18, 19] and similarly shows a decreasing trend over time, moving from 30% in 2000–2005, to 17% during (2006–2010) and 14% from 2011 to 2016. This is, most likely, due to the referral of the most severely affected families in the first years of cancer genetic services, and the use of less strict inclusion criteria in the later period, given the decrease in cost of the molecular analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mutations in BRCA1 and BRCA2 genes were identified in 16% of families (26% of individuals) included in the high-risk HBOC sample. This rate is comparable with other studies [14, 18, 19] and similarly shows a decreasing trend over time, moving from 30% in 2000–2005, to 17% during (2006–2010) and 14% from 2011 to 2016. This is, most likely, due to the referral of the most severely affected families in the first years of cancer genetic services, and the use of less strict inclusion criteria in the later period, given the decrease in cost of the molecular analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Nineteen per cent (10/52) of pathogenic variants were recurrent and were responsible of 50% of HBOC families (Additional files 2 and 3: Tables S1 and S2). Many common mutations in Navarra are also frequent in other Spanish populations [1418]. More so, many of the recurrent mutations in Navarra coincide with the most frequent BRCA1/2 variants in Spain, as published in a recent international study [30].…”
Section: Discussionmentioning
confidence: 94%
“…It is also known as 187delAG, this variant is one of three main pathogenic founder variants in the Ashkenazi Jewish population [ 47 ]. In Morocco, this variant has been reported by Zoure et al [ 48 ] and Jouali et al [ 38 ] and globally, it has been found in different populations [ 49 51 ].…”
Section: Discussionmentioning
confidence: 85%
“…Next, 26 publications were further excluded for insufficient data ( n = 15), feline mammary focus ( n = 2), and non-original research ( n = 9) after carefully examining the full texts of the remaining 42 publications. Finally, 16 eligible publications were included in the study of meta-analysis (Haffty et al, 2006 ; Atchley et al, 2008 ; Kwong et al, 2009 ; Arun et al, 2011 ; Comen et al, 2011 ; Gonzalez-Angulo et al, 2011 ; Xu et al, 2012 ; Noh et al, 2013 ; Li et al, 2014 ; Yu et al, 2014 ; Zugazagoitia et al, 2014 ; Aleskandarany et al, 2015 ; Gabaldó Barrios et al, 2017 ; Ghouadni et al, 2017 ; Ha et al, 2017 ; Krammer et al, 2017 ). The screening method and results of the relevant studies are shown in Figure 1 and the main characteristics of participated patients are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%